Gastrointestinal manifestations of COVID-19 in pediatric age - Queirós,Joana (2022)
Abstract Introduction: Gastrointestinal (GI) symptoms associated with COVID-19 have become increasingly relevant, particularly in pediatric age. The expression of angiotensin II receptors in the GI tract may explain, not only the predominance of GI symptoms, but also the presence of isolated GI manifestations of the disease in some cases. The aim of this study was to characterize a population of pediatric patients with COVID-19 and investigate the association of this disease presentation with GI involvement and disease severity. Methods: Retrospective, observational study of pediatric patients with positive SARS-CoV-2 polymerase chain reaction (PCR) testing between March 2020 and September 2021. Data was retrieved from patients’ clinical records. Results: A total of 241 patients were included, 132 (54.7%) of whom male, with a median age of 48 months (interquartile range [IQR] 10-144 months). The disease had multiple presentations, including at least one GI complaint in 39.4% of patients and exclusive GI symptoms in 3.3%. GI involvement significantly correlated with patients’ age, being more frequent in younger children (p=0.001), and with fever (p=0.001). In the group with GI involvement, 86 patients (90.5%) had mild, 7 (7.4%) moderate, and 2 (2.1%) severe disease. Conclusion: COVID-19 GI manifestations occur more frequently in pediatric patients (39.4% in the present study) than in adult counterparts (12% according to the literature). Telephone follow-up made it possible to detect symptoms that could otherwise go unnoticed. Given the wide variety of clinical symptoms, clinicians should keep a high index of suspicion for this infection in young infants presenting with GI symptoms, even in absence of fever.